1985
DOI: 10.1002/jmv.1890150406
|View full text |Cite
|
Sign up to set email alerts
|

AN6520 Ag: An antigen purified from liver with non‐A, non‐B hepatitis

Abstract: An extract prepared from the liver of patient with chronic non-A, non-B (NANB) hepatitis was found to produce a precipitin line in immunodiffusion with a serum from a multiply transfused patient and those from patients convalescent from NANB hepatitis. The antigen was purified by gel filtration and density gradient centrifugation. The antigen had a buoyant density of 1.16-1.20 g/cm3 in cesium chloride, a sedimentation coefficient (S20,w) of 51.5, and a molecular weight of larger than 1.5 X 10(6) daltons. Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We purified the antigen and developed passive hemagglutination assay (PHA) using antigen-coated erythrocytes to detect antibody in patients' sera. We found that the antigen is composed of particles with molecular weight of more than 1.5 × 10 6 Da and diameter of 29-34 nm. The antibody was detected in 37.5% in NANBH cases, but not in control groups [6].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We purified the antigen and developed passive hemagglutination assay (PHA) using antigen-coated erythrocytes to detect antibody in patients' sera. We found that the antigen is composed of particles with molecular weight of more than 1.5 × 10 6 Da and diameter of 29-34 nm. The antibody was detected in 37.5% in NANBH cases, but not in control groups [6].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the antigen is composed of particles with molecular weight of more than 1.5 × 10 6 Da and diameter of 29-34 nm. The antibody was detected in 37.5% in NANBH cases, but not in control groups [6]. Then we developed monoclonal antibodies (mAbs) and used one of them, 1F12, to develop radioimmunoassays (RIAs) for the antigen and for the patient's antibody [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations